2006
DOI: 10.1159/000093890
|View full text |Cite
|
Sign up to set email alerts
|

First Trimester Ultrasound Diagnosis of Lethal Multiple Pterygium Syndrome

Abstract: Objective: Diagnosis of lethal multiple pterygium syndrome in the first trimester of pregnancy. Methods: A 38-year-old woman attended our ultrasound (US) clinic at 11.2 weeks gestation. She has had two previous stillbirths affected by lethal multiple pterygium syndrome. Transabdominal and transvaginal US were performed and identified a recurrence. Autopsy findings are compared to the fetal US findings. Results: Fetal US showed a markedly increased nuchal translucency, fixed flexion deformities of the elbows an… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
8
0

Year Published

2009
2009
2019
2019

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 16 publications
(8 citation statements)
references
References 33 publications
0
8
0
Order By: Relevance
“…Previous studies have described first-trimester diagnosis of multiple limb abnormalities, including long bone shortening or aplasia, absent digits, syndactyly, abnormal positioning of wrists and ankles, club hands and feet, overlapping digits, and fused lower extremities. 7,9,[19][20][21][22][23] McEwing et al 7 previously reported the earliest diagnosis of osteogenesis imperfecta type II (9 weeks 3 days), also included in this study. 7 Our data corroborate these findings with the detection of absent limbs (Figures 3 and 4), shortened or missing long bones (Figures 2 and 5), fused extremities, club hands and feet (Figure 1), clenched hands, and overlapping digits ( Figure 6).…”
Section: Discussionmentioning
confidence: 99%
“…Previous studies have described first-trimester diagnosis of multiple limb abnormalities, including long bone shortening or aplasia, absent digits, syndactyly, abnormal positioning of wrists and ankles, club hands and feet, overlapping digits, and fused lower extremities. 7,9,[19][20][21][22][23] McEwing et al 7 previously reported the earliest diagnosis of osteogenesis imperfecta type II (9 weeks 3 days), also included in this study. 7 Our data corroborate these findings with the detection of absent limbs (Figures 3 and 4), shortened or missing long bones (Figures 2 and 5), fused extremities, club hands and feet (Figure 1), clenched hands, and overlapping digits ( Figure 6).…”
Section: Discussionmentioning
confidence: 99%
“…[45] However, many other chromosomal syndromes may also present these ultrasound markers. [6] For this reason, in most cases, it is only possible to suspect LMP at a more advanced stage of pregnancy, when the joint contractures become more evident, along with absence of normal fetal movement.…”
Section: Discussionmentioning
confidence: 99%
“…The presence of increased nuchal translucency or nuchal oedema and hydrops, lung hypoplasia, pterygia, oligo‐/polyhydramnios, growth restriction, CNS malformations including microcephaly and enlargement of ventricles are usually indicative for a severe, often lethal, condition, particularly if detected in the first or early second trimester (Ajayi, Keen, & Knott, ; Gundogan, Fong, Keating, Pierre‐Louis, & Chitayat, ; Hall, , ; Hoellen et al, ). AMC may also occur in association with isolated brain malformations as a consequence of neurological dysfunction.…”
Section: The Clinical Approach To Determine the Etiology Of Amc In Prmentioning
confidence: 99%